Regulators of aerobic and anaerobic methane oxidation in two pristine temperate peatland types - Nweze, Justus Amuche; Tláskal, Vojtěch; Wutkowska, Magdalena; Meador, Travis B; Picek, Tomáš; Urbanová, Zuzana; Daebeler, Anne (FEMS microbiology ecology, 2024)
Despite covering <5% of Earth's terrestrial area, peatlands are crucial for global carbon storage and are hot spots of methane cycling. This study examined the dynamics of aerobic and anaerobic methane oxidation in two undisturbed peatlands: a fen and a spruce swamp forest. Using microcosm incubations, we investigated the effect of ammonium addition, at a level similar to current N pollution processes, on aerobic methane oxidation. Our findings revealed higher methane consumption rates in fen compared to swamp peat, but no effect of ammonium amendment on methane consumption was found. Members of Methylocystis and Methylocella were the predominant methanotrophs in both peatlands. Furthermore, we explored the role of ferric iron and sulfate as electron acceptors for the anaerobic oxidation of methane (AOM). AOM occurred without the addition of an external electron acceptor in the fen, but not in the swamp peat. AOM was stimulated by sulfate and ferric iron addition in the swamp peat and inhibited by ferric iron in the fen. Our findings suggest that aerobic methane oxidizers are not N-limited in these peatlands and that there is an intrinsic potential for AOM in these environments, partially facilitated by ferric iron and sulfate acting as electron acceptors.
Keywords: Ammonium Compounds; anaerobióza; Anaerobiosis; Sulfates; aerobióza; Aerobiosis; oxidace-redukce; Methane; půda; Methylocystaceae; Soil Microbiology; greenhouse gas emissions; mokřady; ammonium; electron acceptors; půdní mikrobiologie; Oxidation-Reduction; methanotrophic bacteria; Soil; Wetlands; methan; amoniové sloučeniny; sírany